Ropivacaine combined with esketamine in ultrasound-guided thoracic paravertebral nerve block in lung cancer patients undergoing thoracoscopic radical surgery - Jian Wen; Gao Zhou; Yong Bin; Yan Zeng; Dianxiang Tan; Juan Zhang (Discover Oncology)
Abstract Objective We aim to evaluate the analgesic efficacy of ultrasound-guided thoracic paravertebral nerve block (TPVB) using ropivacaine combined with esketamine in lung cancer patients undergoing thoracoscopic radical surgery. Methods This retrospective study included clinical data from 74 lung cancer patients who underwent thoracoscopic radical surgery between January 2023 and June 2024. Patients were divided into two groups based on their analgesic regimen: the control group received standard general anesthesia, while the observation group received ultrasound-guided TPVB with ropivacaine combined with esketamine. General clinical parameters, changes in mean arterial pressure (MAP) and heart rate (HR), postoperative pain scores, serum pain mediator levels, time to awakening, time to mobilization, and duration of hospitalization, and incidence of adverse reactions were compared in two groups. Results There were no significant differences between the two groups in terms of operation time, intraoperative bleeding, or dosages of sufentanil and remifentanil. Compared to the control group, the observation group showed lower MAP and HR at the completion of the operation. Additionally, Visual Analog Scale scores and serum levels of Neuropeptide Y, Substance P, and dopamine were also lower in the observation group. The postoperative time to awakening, time to mobilization, and duration of hospitalization were shorter in the observation group. No significant differences were observed in the incidence of adverse reactions between the two groups. Conclusion Ultrasound-guided TPVB with ropivacaine and esketamine provides superior postoperative analgesia in lung cancer patients undergoing thoracoscopic radical surgery. This approach effectively reduces physiological stress responses, promotes faster recovery, and does not increase the risk of adverse events.